Recognizing the Multitude of Housing Barriers Facing Homeless and Unstably Housed Survivors of Intimate Partner Violence - Lopez-Zeron, Gabriela; Bilbao-Nieva, M. Isidora; Sullivan, Cris M.; Chiaramonte, Danielle (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2021)
Survivors of intimate partner violence (IPV) seek services from domestic violence (DV) programs for a multitude of reasons. One critical need for many survivors, that has often been overlooked when considering the services DV programs provide, is stable housing. DV programs typically offer safety planning, counseling, advocacy, support groups, and some form of temporary safe housing (e.g., shelter, transitional housing), but increasingly, survivors need assistance securing safe and stable long-term housing. It is imperative, then, that program staff have the information, resources, and skills needed to effectively assist survivors with this essential need. This study examined the housing barriers facing 406 homeless or unstably housed intimate partner violence survivors seeking help from one of five domestic violence programs. In-depth interviews conducted shortly after they sought services revealed that many survivors had a prior history of homelessness, and the vast majority reported at least five issues they faced that made obtaining safe and affordable housing difficult. Findings emphasize the importance of advocates specifically asking about potential housing barriers, and having the knowledge, skills, and community connections needed to effectively assist homeless and unstably housed survivors.